REVIEW JURIDICAL REDISTRIBUTION OF LAND TO THE OBJECT OF LAND IN THE DISTRICT DELI SERDANG - Willy Tanjaya; Yusriando Yusriando; Djevin Septry Liesaputra (Magister Kenotariatan Universitas Pasundan, 2021)
For the State of Indonesia the land is a gift from God Almighty as well as national wealth Land in an agrarian society has a very important positions so it is very necessary for the state and society to mak e the best use of th e land for the welfare of the people for their survival Therefore this discussion is very interesting to study This research is: analyzing the laws and regulations concerning the redistribution of land objects in Indonesia analyzing the implementation of redistribution land object in Deli Serdang Regency analyzing the obstacles experienced in land redistribution for land objects in Deli Serdang Regency Can provide benefits for the development of legal science especially regarding Land Redistribution in Indonesia Practical Benefits is expected to provide useful information useful for the community/readers and Notaries in carrying out their duties related to Land Redistribution of Land Objects in Indonesia Indonesia The theoretical framework used is legal certainty namely providing legal certainty to individuals with the aim of protecting individuals from the arbitrariness of the government or other legal entities.